Lithuanian primers at the end of the nineteenth century to the beginning of the twentieth century - Simaška, K. (Psichologija, 1963)
The history of primers is connected to schools and developments in educational, pedagogical, methodological, and psychological thought, and with children's literature, literary language, and development issues for writing rules.This article provides only a general overview of the primer analysis period in order to show how the primers were improved together the social/cultural conditions.At the end of the nineteenth century in the most difficult conditions of cultural life (a lack of native language books in schools) there were primers created on the basis of syllabication for purposes of the clergy; they were printed abroad. The first Antanas Kriščiukaitis primer consisting of the synthetic acoustic-based approach, which was not religious, was only released in 1895 thanks to the advanced efforts of intellectuals.After the 1905 revolution, there was some noticeable recovery of pedagogical thought following certain cultural improvement. A wide range of primers was published at that time, mostly those of P. Višinskis (1905) and K. Skabeikis (1909), which helped the analytical/synthetic sound method of teaching reading basics. Their content, these primers best complied with the requirements raised by the 1905 Revolution: separate the school and the church, introduce general free education in the native language, etc. These primers were designed for folk schools; they thought neither prayers nor any religious material.The authors of the primers (A. Kriščiukaitis, P. Višinskis, and G. Skabeikis) were heavily influenced in terms of methodological tools by Russian educators, especially L.N. Tolstoy, K.D. Usinsk, V.A. Flerov, and others. These educators' experience was creatively adapted to the conditions of Lithuanian schools.
Keywords: primers; teaching language and writing; history of pedagogy.